The Universities (Discipline Of Staff) Rules: An Administrative Law Perspective - Gan, CC (Journal of Malaysian and Comparative Law, 1994)
This article will attempt to discuss and examine the Discipline of Staff Rules of the local universities which are established under the Universities and University Colleges Act 1971 primarily from the viewpoint of Administrative Law. The discussions and examination will be focused only on the University of Malaya (Discipline of Staff) Rules 1979 as the other local universities established under the UUCA 1971 also possess similar rules.